Language production and comprehension - Dell, Gary (Henry Stewart Talks, 2010)
Nature of language, Language production, Speech errors, Freud, Interactive activation, Aphasia and brain regions involved in semantic errors, Language comprehension, Processing speed and the role of prediction, Prediction and event-related brain potentials, Event-related optical imaging, Prediction during comprehension is a form of production
Reviewed at 2020/05/01